High‑energy treatment of steel billet with coating from high‑strength amorphous alloy - M. N. Vereshchagin; S. I. Kirilyuk (Литьë и металлургия, 2024)
The paper presents temperature profiles at the depth of a steel billet with a coating of an iron-based amorphous alloy under the pulsed effect of laser radiation. With the action of a constant power heat source, the heat propagation process tends towards a limiting quasi-stationary state. The choice of technological modes of laser radiation exposure with a combination of laser beam scanning speed and radiation power is determined. The depth of the molten layer of the billet material during scanning under the condition of obtaining a high-quality product has been established.